LINGUOPOIETIC MEANS IN THE NOVEL”SCORPION FROM THE ALTAR” - Lafasov, Urak (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
Until XX century, the fields of language and literature were studied separately in world scientific research. The field of linguopoetics, which studies the issue of creating an aesthetic effect of stylistically colored language units in the artistic text, was formed to eliminate this gap. The study provides information about Abdulla Kadiri, the creator of Uzbek historical novels in the Uzbek national literature; his historical novels that formed the basis of the sixth national schools of novel writing in the world. It states that Kazakh, Turkmen, Tajik, Karakalpak and Kyrgyz novels were formed in Central Asia because of the new trend started by Abdulla Kadiri. It was emphasized that the national language can reveal the scope of expression and the level of incomparable image.The sound doubling, sound exchange, morphological forms, lexical units (synonyms, antonyms, pure Uzbek words, dialectal words, phraseological units) used in the novel “Mehrobdan Chayan” by the great Uzbek writer Abdulla Kadiri), stylistic tropes (irony, simile, exaggeration, exaggeration), proverbs, heroes’ portraits, replica-repetition, and linguopoetic means were analyzed.